EFEKTIVITAS PELAKSANAAN PARKIR KENDARAAN BERMOTOR DI KOTA BATAM - Oktavia, Roza; Arman, Zuhdi (LPPM Universitas Putera Batam, 2020)
In the city of Batam the numbers of motorized vehicles from year to year has greatly increase, Certainly this be performed by the government in Batam in providing and see parking lot. By the management of the parking lot it would boost local revenue with he was wearing taxes and levies from the use of parking lot. The Purpose of this study is the effectiveness of the implemetation of motorized parking ini the city of Batam. Type research that is used is qualitative data collection method by means of juridical analysis to the regulations prevailing in a city Batam. The data Acquisition techniques applied by the method of sample acquisition, purposive data analysis, reduction of presentation and formulating the conclusion. The results obtained are yhe city government policy in batam in increase their own local revenue accomplishment not ideal, The case is by the rampant illegal parking attendants illegal and adequate parking lot is controlled by private parties or thugs. The solution to the ordinance batam about the mayor of parking change management and fix a groove service facilities including security and comfort.